Enhanced co-digestion of sewage sludge and food waste using novel electrochemical anaerobic membrane bioreactor (EC-AnMBR). (June 2023) - Zhen, Guangyin; Pan, Yang; Han, Yule; Gao, Yijing; Ibrahim Gadow, Samir; Zhu, Xuefeng; Yang, Liying; Lu, Xueqin
Graphical abstract: Highlights: Electrochemical membrane reactor was designed to co-digest sludge and food waste. Functional electroactive microorganisms were proliferated on bioelectrodes. Robust synergy of various microorganisms improved anaerobic co-digestion. 2.76-time increase in methane production was obtained in the optimized conditions. Electrostatic repulsion and electrochemical oxidation mitigated membrane fouling. Abstract: Membrane fouling remains a big challenge hindering the wide-application of anaerobic membrane bioreactor (AnMBR) technology. In this study, an electrochemical anaerobic membrane bioreactor (EC-AnMBR) was developed by coupling electrochemical regulation to enhance co-digestion of sewage sludge and food waste and mitigate membrane fouling. The highest methane production (0.12 ± 0.02 L/Lreactor /day) and net energy recovery (31.82 kJ/day) were achieved under the optimum conditions of 0.8 V, hydraulic retention time of 10 days and solids retention time of 50 days. Electrochemical regulation accelerated the mineralization of high-molecular-weight organics and reinforced the membrane antifouling ability by inducing electrostatic repulsive force and electrochemical oxidation. Besides, symbiotic relationships among functional microorganisms ( Spirochaetes, Methanolinea, etc.) were enhanced, improving the hydrolysis and methanogenesis processes of complex organics and the long-term stability. This study confirms the technical feasibility of EC-AnMBR in treating high-solid biowastes, and provides the fundamental data to support its application in real-world scenarios.